Analysis of two strain probiotics on digestive enzymes, liver function and antimicrobial activity of catfish (Clarias gariepinus) treated with Aeromonas hydrophila - NURUL AINI; SRI PUJI ASTUTI WAHYUNINGSIH; FARAH NISA UZAKKY; CAROLINE BETZY; FATIMAH FATIMAH; SAPTO ANDRIYONO (Society for Indonesian Biodiversity, 2024)
Abstract. Aini N, Wahyuningsih SPA, Uzakky FN, Betzy C, Fatimah, Andriyono S. 2024. Analysis of two strain probiotics on digestive enzymes, liver function and antimicrobial activity of catfish (Clarias gariepinus) treated with Aeromonas hydrophila. Biodiversitas 25: 4333-4339. Catfish (Clarias gariepinus Burchell 1822) is one of the most consumed fish. Good fisheries management is needed to maintain fish stocks. One of the efforts to manage fisheries safely is by using probiotics in the form of Duo Strain Probiotics (DSP). DSP is a probiotic formula consisting of Lactobacillus casei and Bacillus subtilis. The purpose of this study was to determine the effect of DSP on digestive enzyme levels, liver health status, and the potential of catfish blood serum as an antimicrobial agent. The treatments included DSP to the feed with concentrations of 0%, 5%, 10% and 15% using Aeromonas hydrophila infection. The results showed no significant change in amylase enzyme level between DSP treatments of various concentrations and the control treatment. DSP treatment of 10% and 5% in the non-infected fish group was the best treatment for increasing the level of protease and lipase enzymes, respectively. For liver health status parameters, 15% DSP treatment was the best treatment that could suppress the production of AST and ALT enzymes in fish blood serum. Catfish blood serum infected with pathogens and treated with 15% DSP has the ability as an antibacterial agent against A. hydrophila.